Studi Perbandingan Modal Sosial Pada Tipe Keluarga Bajo di Desa Mantigola Kecamatan Kaledupa Kabupaten Wakatobi - Kamal, Dita Septiani; Mardin, Mardin; Wianti, Nur Isiyana (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This study aims to determine the differences in social capital in the three types of families in Mantigola village and family type that will be vulnerable to social capital. Data processing that has been obtained using qualitative analysis using the daily diary of research results then reduced and analyzed through livelihood capital (social capital). The results of this study indicate the differences in social capital owned by each type of family. The extended family (extended family) is a very strong family on all aspects of social capital. The nuclear family will be vulnerable to social capital based on the social status on the part of ascribing status and social networking based on the relationship of social capital, and the widow family (single family) of the most vulnerable families as the single family is only strong in social capital. Social networking on the part (social capital bond)